Main epidemics that struck Peru during the Viceroyalty according to Ricardo Palma’s Tradiciones peruanas - Carbajal Cerazo, Georgeo Stefano (2020)
This article will analyse the stories «Un cerro que tiene historia», «Muerte en vida» and «Los polvos de la condesa». It is proposed that in these texts Ricardo Palma describes the various epidemics that occurred between the 17th and 18th centuries, causing the death of thousands of people. It also shows the discoveries in medicine resulting from these events, as well as the use of vaccines in the eradication of epidemics.